The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11095-016-1904-6
|View full text |Cite
|
Sign up to set email alerts
|

A Tunable, Biodegradable, Thin-Film Polymer Device as a Long-Acting Implant Delivering Tenofovir Alafenamide Fumarate for HIV Pre-exposure Prophylaxis

Abstract: Purpose The effectiveness of Tenofovir based HIV pre-exposure prophylaxis (PrEP) is proven, but hinges on correct and consistent use. User compliance and therapeutic effectiveness can be improved by long acting drug delivery systems. Here we describe a thin-film polymer device (TFPD) as a biodegradable subcutaneous implant for PrEP. Methods A thin-film polycaprolactone (PCL) membrane controls drug release from a reservoir. To achieve membrane controlled release, TAF requires a formulation excipient such as P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 21 publications
3
90
0
Order By: Relevance
“…A single oral dose of only 10 mg of EFdA in humans inhibited replication for at least 1 week, 17 and studies in rats involving an implant suggested that greater than 6 months' release of EFdA at adequate levels may be feasible 17 . Although EFdA is only in early-stage development, TAF is another NRTI that is already approved as an oral agent and is now being explored as an agent to be released from several different types of long-acting implants 18 , 19 . And GS-9131 is an early-stage NRTI prodrug with a structure and potency somewhat similar to TAF, but with a very robust barrier to resistance and unique resistance profile 15 .…”
Section: New Arvs May Help Overcome These Downsidesmentioning
confidence: 99%
See 1 more Smart Citation
“…A single oral dose of only 10 mg of EFdA in humans inhibited replication for at least 1 week, 17 and studies in rats involving an implant suggested that greater than 6 months' release of EFdA at adequate levels may be feasible 17 . Although EFdA is only in early-stage development, TAF is another NRTI that is already approved as an oral agent and is now being explored as an agent to be released from several different types of long-acting implants 18 , 19 . And GS-9131 is an early-stage NRTI prodrug with a structure and potency somewhat similar to TAF, but with a very robust barrier to resistance and unique resistance profile 15 .…”
Section: New Arvs May Help Overcome These Downsidesmentioning
confidence: 99%
“…While developing such biodegradable implants has long been a goal for long-acting reversible contraception, it has proved elusive due to several potential challenges, including a prolonged tail of low levels of the active agent and the possibility of dumping large amounts of the agent when the implant terminally biodegrades. However, new designs for biodegradable implants may overcome these challenges for ARVs, such as a thin-film polymer device that contains a thin biodegradable coat and a reservoir filled with an ARV (TAF, noted above, is an ARV that is being used in one investigational device) 18 . The ARV diffuses through the membrane, allowing the reservoir to gradually empty after which the outer coat biodegrades, thereby decoupling the biodegradation from the release and hopefully avoiding dumping or a prolonged tail.…”
Section: Implants That Are Easier To Implement: Biodegradable and Refmentioning
confidence: 99%
“…For example, long-acting injectable antiretrovirals, rilpivirine and cabotegravir, have shown promising results for treatment of HIV in phase 2 clinical trials [93]. Implants embedded with long-acting antiretrovirals are also under development [94,95]. If successful, such long-acting antiretroviral formulations for HIV treatment could be combined with contraceptives for pregnancy prevention.…”
Section: Future Contraceptive Optionsmentioning
confidence: 99%
“…Other PrEP products (e.g. dapivirine, tenofovir alafenamide (TAF), and maraviroc rings, biodegradable tenofovir (TFV) films, cabotegravir injections, TAF or maraviroc pills, TFV implants), are at various stages of the research and development process and are promising, longer-acting HIV prevention options (9 ■ ,10 ■ ,11 ■ ,12). However, it has recently been hypothesized that the efficacy of topically-applied PrEP products may be moderated by vaginosis dysbiosis, a general term indicating that vaginal microbiota are sub-optimal (13 ■■ ).…”
Section: Introductionmentioning
confidence: 99%